EMI Shielding Performance of Reduced Graphene Oxide/PES-C Composite Film with Sandwich Structure. Issue 1 (1st March 2022) - Wang, Haidong; Li, Wei; Li, Jiaying; Qiu, Wenwen; Pang, Daming; Xing, Yi; Tong, Xingyu
Abstract: In this paper, a reliable and convenient hot-pressing method has been utilized to produce reduced graphene oxide (RGO)/PES-C composite film with sandwich structure, which possesses excellent electromagnetic interference shielding performance of an average electromagnetic shielding effectiveness value of 37.96 dB in the X-band. The gas-liquid interfacial self-assembly method was used to prepare graphene oxide films and the films were then reduced by the combination of hydroiodic acid and microwave irradiation to obtain microwave-assistant hydroiodic acid reduced graphene oxide (MA-HIA-RGO) films. Finally, the MA-HIA-RGO and PES-C films were compounded together to obtain the sandwich structure. The influence of the reduction method on the electromagnetic interference shielding performance of the composite film was discussed. Compared with the traditional method of uniformly scattering graphene into the resin, this method does not require complicated procedures and demanding conditions to prevent the agglomeration of graphene.